Post-Operative Macular Oedema Management Through Ayurveda- A Case Study (AYUSHDHARA, 2023)
Macular oedema is gush of fluid from surrounding vessels of foveal region into tissues which makes pocket or vesicle like spaces and increases thickness of macula which can be checked by Fluorescein angiography and autofluorescence. Blurry or wavy vision near or in the centre of field of vision is its primary symptom. Chronic inflammation, direct macular traction, and decrease in oxygen amount’s common role is assessed in every study till now. Main Clinical Findings: A female patient of age 66 years had been complaining of blurred vision and discomfort in left eye for 3months after her cataract surgery. Diagnosis: She was diagnosed for macular oedema and treated for it. Interventions: The principles of Vataja Timira, Shotha were followed and internal medicine was given. Outcome: Patient got Significant results by improving quality of vision and repair the detached area. Conclusion: The present case anticipates the fruitful approach of Ayurveda science in dealing with Macular oedema. This also confirms relation between macular oedema and treatment principles followed.